2020
DOI: 10.1155/2020/9268083
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates Chronic Unpredictable Mild Stress-Induced Depressive-Like Behaviors via Restoring Changes in Oxidative Stress and the Activation of Nrf2 Signaling Pathway in Rats

Abstract: Accumulating evidence has demonstrated that oxidative stress is associated with depression. Our present study aimed at investigating the antidepressant effect and the possible mechanisms of curcumin (CUR) in chronic unpredictable mild stress- (CUMS-) induced depression model in rats. After exposure to CUMS for four weeks, the rats showed depressive-like behavior, and the depressive-like behaviors in CUMS-treated rats were successfully corrected after administration of CUR. In addition, CUR could effectively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 61 publications
4
64
0
Order By: Relevance
“…19 Furthermore, our results are in line with previous studies indicating the downregulation of both Nrf2 and its downstream protein HO-1 in a depression model. 61 Interestingly, increased levels of ROS and LPO, along with the downregulation of Nrf2/HO-1, were markedly recovered in carvacrol-treated animals, validating our proposed hypothesis that carvacrol exerts free-radical scavenging and antioxidant activity. We previously reported the antioxidant effect of a similar monoterpene carveol in ischemic stroke by targeting the Nrf2.…”
supporting
confidence: 80%
“…19 Furthermore, our results are in line with previous studies indicating the downregulation of both Nrf2 and its downstream protein HO-1 in a depression model. 61 Interestingly, increased levels of ROS and LPO, along with the downregulation of Nrf2/HO-1, were markedly recovered in carvacrol-treated animals, validating our proposed hypothesis that carvacrol exerts free-radical scavenging and antioxidant activity. We previously reported the antioxidant effect of a similar monoterpene carveol in ischemic stroke by targeting the Nrf2.…”
supporting
confidence: 80%
“…Inhibition of CaMKIIβ-ERK1/2-CREB signaling mediates the chronic ketamine use-associated cognitive impairments by restraining synaptic signaling ( Luo et al, 2020 ). Supplementation of curcumin increases the ratio of pCREB to CREB and corrects the depressive-like behaviors successfully in CUS-treated rats ( Liao et al, 2020 ). CREB signaling, which is inhibited by over-activated GluN2B, participates in the antidepressant-like effects of ketamine, and extrasynaptic CaMKIIα is also involved in the CREB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that HO-1 has proproliferative effects in endothelial cells and some tumor cells, while the antiproliferative effects in vascular and airway smooth muscle cells have also been proven [44][45][46][47]. NQO-1 and HO-1 are important antioxidant enzymes in the Nrf2-ARE pathway, and NQO-1 regulates the cellular stress response by reducing quinone [48,49]. Normally, Nrf2 is located in the cytoplasm and translocates into the nucleus after stimulation.…”
Section: Discussionmentioning
confidence: 99%